IDENTIFIKASI ALAT TANGKAP IKAN RAMAH LINGKUNGAN DI DESA BAGAN ASAHAN KECAMATAN TANJUNG BALAI (Identification of environmentally fishing gear in Bagan Asahan Village, sub-district Tanjung Balai) - Aznia Marlina Sima; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2014)
District Asahan has a large fishery resources. This is supported by the District Asahan shoreline reach to ± 58 km. Bagan Asahan Village sub-district of Tanjung Balai is located at the mouth of the Asahan river directly opposite with the Strait of Malacca. Fisherman from Bagan Asahan Village cath fisher by using gears. The most widely fishing gears were gill net, bottom gill net, longline, fishing rod, and traps (bubu). The purpose of this research was to identify fishing gear, included in the category of environmentally friendly or not and to find out the production of the fishing gear.Fishing gear used by fisherman of Bagan Asahan Village sub-district Tanjung Balai including a very environmentally friendly fishing gear and environmentally friendly. The result of research showed gill net fishing gear and fishing rod that very environmentally friendly while the bottom gill net, longline, and traps including gear type of environmentally friendly. Production result were obtained each gearas follows. Gill net was 509.7 kg/, bottom gill net was 1469.2 kg/month, longline and fishing grod was 404.89 kg/month and traps (bubu) was 959.6 kg/month.Keywords : Bagan Asahan Village, Fishing gears, Yield obtained.